Effect of energy dissipating devices on storey drift and displacement by nonlinear time history analysis. (2015) - MagarPatil, H.R.; Jangid, R.S.
The seismic vulnerability of steel moment resisting frame with passive dampers is assessed with 13 different seismic resisting systems. The structural frames are analysed and designed for the loading conditions in Pune. The stiffness effect on the stories is demonstrated through the lateral displacement profile of the building. Hybrid passive dampers with buckling restrained brace of mild steel and aluminium are used to improve lateral stiffness of the structure. Mild steel braces have increased lateral strength and proved to be good energy dissipating devices. The aluminium sections are chosen as energy dissipating device due to its low yield strength. Aluminium buckling restrained braces has improved performance of the structure in the form of reduced storey drift and displacement as compared to basic steel moment resisting frame. By the use of these devices either alone or in combination with BRB, the performance of SMRF has been improved significantly.